2018
DOI: 10.3389/fpls.2018.00869
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Convenient Method for Early Warning of Algal Cell Density by Chlorophyll Fluorescence Parameters and Its Application in a Highland Lake

Abstract: The occurrence of algal blooms in drinking water sources and recreational water bodies have been increasing and causing severe environmental problems worldwide, particularly when blooms dominated by Microcystis spp. Bloom prediction and early warning mechanisms are becoming increasingly important for preventing harmful algal blooms in freshwater ecosystems. Chlorophyll fluorescence parameters (CFpars) have been widely used to evaluate growth scope and photosynthetic efficiency of phytoplankton. According to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…For example, Woo et al [10] found many marine-derived phylotypes during summer, with Chlorophyta dominating their samples. These are a taxon of green algae, for which previous literature suggests Chlorophyll-∝ as the dominant fluorophore [34]. Neither the PLAIR Rapid-E nor the WIBS-NEO are suited to algal identification because Chlorophyll-∝ has a much higher excitation wavelength of 400-485 nm [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Woo et al [10] found many marine-derived phylotypes during summer, with Chlorophyta dominating their samples. These are a taxon of green algae, for which previous literature suggests Chlorophyll-∝ as the dominant fluorophore [34]. Neither the PLAIR Rapid-E nor the WIBS-NEO are suited to algal identification because Chlorophyll-∝ has a much higher excitation wavelength of 400-485 nm [35].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several kinds of deep learning models are usually utilised in time-series forecasting, for instance, RNN and its variant LSTM. RNN has been suggested to elucidate the dynamics [64], [65]. It is a network with feedback connections from the hidden and output layers to the preceding ones, through which the dynamics of sequential data can be recorded, and the memories of the prior patterns are kept via cycles in the network.…”
Section: Data-driven Algal Growth Prediction Methodsmentioning
confidence: 99%
“…Mean and maximum depth are 10.5 and 20.5 m, respectively. Lake Erhai, is currently in the early stages of eutrophication (Lin et al, 2016;Wang et al, 2018), with concentration of total nitrogen (TN) of 0.7 mg/L (Zhu et al, 2018), total phosphorus (TP) of 0.03 mg/L (Zhu et al, 2018) and chlorophyll a (Chl a) of 13.33 µg/L during June 2013 to May 2015, with a peak value exceeding 30 µg/L (Wang et al, 2018), all of which exceed the threshold value of the eutrophication categories (TP > 0.03 mg/L, TN > 0.65 mg/L, and Chl a > 9 µg/L, Nürnberg, 1996). Samples were collected monthly, from 15 locations, between January 2012 and December 2014 ( Figure 1).…”
Section: Study Site and Sampling Methodsmentioning
confidence: 99%